WOMEN'S CRICKET IN INDIA: AN OVERVIEW - Laxmikanthrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women's cricket in India has failed to make a mark at international level. Some of the hurdles in the popularization and development of women's cricket in India are discrimination in the availability of facilities, financial benefits, awards, the number of matches played and failure in promotion of cricket for women at the school level. Furthermore, adequate attention is not given to cricket at the college/university level. The study will help to plan the strategies to overcome the problems of women's cricket in India through improving its status by creating awareness regarding the game. The study will inspire schools, colleges and private cricket academies to increase their role for the development of women cricket by providing separate facilities, equipment, qualified coaches and necessary provisions for women cricketers. The study will bring awareness to the governing bodies at various levels and encourage them to change their attitude towards women's cricket.